The Influence of Perceived Quality, Perceived Ease of Use, and Perceived Transaction Security on User Satisfaction in Flip Application (A Study on the Millennial Generation and Generation Z) - Veronica Mechy Luklu'ul Firdaus; R. Yuniardi Rusdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of technology, especially information technology, has penetrated various sectors in Indonesia, from education to banking. With this, banking access can be used by all groups flexibly through fintech services. Flip is a real example of how technology services can collaborate with the banking sector to expand the reach of its services. Flip. The application helps its users to make free interbank transfers, send money abroad via Flip Globe, top up e-wallets, pay electricity bills, buy electricity tokens, top up credit, buy data packages, Internet & TV, BPJS Health, Credit Installments at affordable costs. This study aims to test the effect of perceived quality, perceived ease of use, and perceived transaction security on user satisfaction in the flip application (a study of the millennial generation and generation z). The population in this study were all residents in the city of Surabaya who had made transactions using the Flip application. The data collection method was through a survey using a questionnaire to 155 respondents with a non-probability sampling method through Purposive Sampling. Data analysis techniques include testing validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, F test and t test. The results showed that simultaneously the variables perceived quality, perceived ease of use, and perceived transaction security have a significant effect on user satisfaction. Partially perceived ease of use and perceived transaction security have a significant positive effect on user satisfaction, while perceived quality has a positive but insignificant effect.